2001
DOI: 10.2337/diabetes.50.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Decreased Oxygen Tension in Transplanted Rat Pancreatic Islets Irrespective of the Implantation Site

Abstract: In this study, we syngeneically transplanted islets to three different implantation sites of diabetic and nondiabetic rats, then 9 -12 weeks later we measured the blood perfusion and compared the tissue partial pressure of oxygen (PO 2 ) levels of these transplanted islets to endogenous islets. Modified Clark microelectrodes (outer tip diameter 2-6 m) were used for the oxygen tension measurements, and islet transplant blood perfusion was recorded by laser-Doppler flowmetry (probe diameter 0.45 mm). The islet g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
307
3
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(320 citation statements)
references
References 54 publications
7
307
3
3
Order By: Relevance
“…At the time of transplantation, 250 (rat) or 200 (mouse) freshly isolated (<4 h after pancreas extirpation) or cultured (4-7 days of culture) islets were packed in a braking pipette and implanted beneath the renal capsule on the dorsal side of the left kidney of syngeneic normoglycaemic rats that had been anaesthetised with pentobarbital (60 mg/kg, i.p., Apoteket, Umeå, Sweden) or of syngeneic alloxan-diabetic mice that had been anaesthetised with Avertin (0.02 ml/g i.p, of a 2.5% [vol/vol] solution of 10 g 97% [vol/vol] 2,2,2,-tribromoethanol [Sigma-Aldrich] in 10 ml of 2-methyl-2-butanol [Kemila, Stockholm, Sweden]). For practical reasons, normoglycaemic rats were, used as recipients in the engraftment studies, since there is no difference in revascularisation and oxygenation of transplanted islets, compared to when the islets are implanted to cure diabetic recipients instead [19,24]. In all cases exocrine contamination of the transplanted islets was avoided as much as possible, since this has previously been observed to have a negative influence on the engraftment process of transplanted islets [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of transplantation, 250 (rat) or 200 (mouse) freshly isolated (<4 h after pancreas extirpation) or cultured (4-7 days of culture) islets were packed in a braking pipette and implanted beneath the renal capsule on the dorsal side of the left kidney of syngeneic normoglycaemic rats that had been anaesthetised with pentobarbital (60 mg/kg, i.p., Apoteket, Umeå, Sweden) or of syngeneic alloxan-diabetic mice that had been anaesthetised with Avertin (0.02 ml/g i.p, of a 2.5% [vol/vol] solution of 10 g 97% [vol/vol] 2,2,2,-tribromoethanol [Sigma-Aldrich] in 10 ml of 2-methyl-2-butanol [Kemila, Stockholm, Sweden]). For practical reasons, normoglycaemic rats were, used as recipients in the engraftment studies, since there is no difference in revascularisation and oxygenation of transplanted islets, compared to when the islets are implanted to cure diabetic recipients instead [19,24]. In all cases exocrine contamination of the transplanted islets was avoided as much as possible, since this has previously been observed to have a negative influence on the engraftment process of transplanted islets [25].…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies suggest that endothelial cells originating from the donor may also contribute significantly, and be important for the revascularisation process [16,17]. In our previous studies, we have observed that grafts composed of cultured rodent or human islets are not sufficiently revascularised, which results in a low graft oxygen tension and tissue acidosis [18][19][20][21][22]. The present study tested the hypothesis that syngeneic islet grafts composed of freshly isolated rodent islets become more efficiently revascularised than islets transplanted after culture, and that this might result in an improved islet graft function.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that regulated insulin secretion in these grafts was small, with lowering of blood glucose levels in the animals being largely the result of constitutive release of insulin. This functional difference between the cells in vitro and in vivo may be caused by the effects of transplantation, such as lower levels of oxygen, 23 which are critical for insulin secretion. When the cells in the grafts were removed from the mice and cultured in vitro, the insulin content was similar to that of untransplanted cells, 5.1-5.6 pmol/10 6 cells.…”
Section: Insulin Content and Secretionmentioning
confidence: 99%
“…The liver as transplantation side is considered to be a major contributor to these low success rates. Inadequate revascularization,5 the large numbers of natural killer T cells in the liver,6 high concentrations of immunosuppressive drugs,7, 8 and the instant blood‐mediated inflammatory reaction9 play a role in islet graft failure after intraportal transplantation. Therefore, a more adequate transplantation site is required for this technology to gain widespread acceptance and practice.…”
Section: Introductionmentioning
confidence: 99%